Analisis Laporan Arus Kas Pada PT. Garuda Indonesia, Tbk - Syafira Ramadhani; Wendy Wenaldo; Ratih Kusumastuti (Universitas Kristen Indonesia Toraja, 2023)
The company is a form of body or organization that was founded by a person or group. The company's activity is to carry out production which is then distributed in order to meet economic needs. companies in carrying out their operations require substantial funding, therefore the company needs to know the development of its business from time to time so that it can be known whether the company is experiencing progress or setbacks. To be able to find out about this, the owner of the company can look through the accountability report of the company's leadership in the form of financial reports. One of the company's financial reports is the cash flow statement. Cash presents systematically information about cash receipts and disbursements during a certain period. In the statement of cash flows, cash receipts and disbursements are classified according to operations, financing activities and investing. performance.